New assays for carbamyl phosphate synthetase applicable in the presence of exogenous carbamyl phosphate. - D. L. Rigby; A. J. Baron; A. Radford (Fungal Genetics Reports, 1982)
New assays for carbamyl phosphate synthetase applicable in the presence of exogenous carbamyl phosphate.